Sequence-Dependent Self-Assembly and Structural Diversity of Islet Amyloid Polypeptide-Derived β-Sheet Fibrils - Wang,ST; Lin,Y; Spencer,RK; Thomas,MR; Nguyen,AI; Amdursky,N; Pashuck,ET; Skaalure,SC; Song,C; Parmar,PA; Morgan,RM; Ercius,P; et al. (ACS Nano, 2017)
Determining the structural origins of amyloid fibrillation is essential for understanding both the pathology of amyloidosis and the rational design of inhibitors to prevent or reverse amyloid formation. In this work, the decisive roles of peptide structures on amyloid self-assembly and morphological diversity were investigated by the design of eight amyloidogenic peptides derived from islet amyloid polypeptide. Among the segments, two distinct morphologies were highlighted in the form of twisted and planar (untwisted) ribbons with varied diameters, thicknesses, and lengths. In particular, transformation of amyloid fibrils from twisted ribbons into untwisted structures was triggered by substitution of the C-terminal serine with threonine, where the side chain methyl group was responsible for the distinct morphological change. This effect was confirmed following serine substitution with alanine and valine and was ascribed to the restriction of intersheet torsional strain through the increased hydrophobic interactions and hydrogen bonding. We also studied the variation of fibril morphology (i.e., association and helicity) and peptide aggregation propensity by increasing the hydrophobicity of the peptide side group, capping the N-terminus, and extending sequence length. We anticipate that our insights into sequence-dependent fibrillation and morphological diversity will shed light on the structural interpretation of amyloidogenesis and development of structure-specific imaging agents and aggregation inhibitors.